Investigation of photovoltaic thermoelectric air-conditioning system for room application under tropical climate - Looi, K.K. (Korean Society of Mechanical Engineers, 2020)
Photovoltaic thermoelectric air-conditioning system (PT A/C) system could be a greater option compared to conventional A/C system as it is Freon-free and absence of moving parts. This study investigated the cooling and dehumidification performance of a PT A/C that is solely powered by solar energy under tropical climate conditions. The system is built with 9 pieces of thermoelectric to provide cooling for a test chamber of 3.6 m3 volume. The effect of input current on the systemâs cooling and moisture removal rate were investigated and results showed that 5 A is the optimum current level, providing an average of 181 W cooling capacity and 0.14 ltr/hour of moisture removal rate at the given ambient conditions. During the operation, indoor temperature of the test chamber was 4 Â°C lower than the unconditioned chamber and 7.7 Â°C compared to the ambient temperature. Whereas the indoor relative humidity varies between 58~83 . Furthermore, for a 12 hours operation, the system consumes 1.45 kWh of energy, and delivered temperature between 23.8 to 27.8 ÂºC at 5 A. Â© 2020, The Korean Society of Mechanical Engineers and Springer-Verlag GmbH Germany, part of Springer Nature.